Comparative Efficacy, Safety, and Costs of Sorafenib vs. Sunitinib as First-Line Therapy for Metastatic Renal Cell Carcinoma: A Systematic Review and Meta-Analysis - Deng, Huan; Liu, Wenfeng; He, Ting; Hong, Zhengdong; Yi, Fengming; Wei, Yiping; Zhang, Wenxiong (Frontiers in Oncology, 2019)
Purpose: Sorafenib and sunitinib are extensively used as first-line medications for metastatic renal cell carcinoma (mRCC). This meta-analysis was conducted to assess the anti-tumor efficacy, toxicity, and costs of the two drugs among mRCC patients. Materials and Methods: PubMed, ScienceDirect, Scopus, Web of Science, Ovid MEDLINE, the Cochrane Library, Embase, and Google Scholar were searched for eligible articles. The endpoints consisted of progression-free survival (PFS), overall survival (OS), objective response rate (ORR), adverse effects (AEs), and per-patient-per-month (PPPM) costs. Results: We included 14 studies with 2925 patients. Both drugs were valid for treating mRCC with equivalent PFS (hazard ratio [HR]=0.98, 95% confidence interval [CI]: 0.88-1.10, P=0.74) and disease control rates (DCR, risk ratio [RR]=1.03, 95% CI: 0.98–1.08, P=0.28), but sunitinib had a better OS (HR=1.10, 95% CI: 1.01-1.20, P=0.04) and higher ORR (HR=0.66, 95% CI: 0.45-0.97, P=0.03) than sorafenib. Furthermore, sunitinib induced more incidences of severe hematologic AEs (anemia, neutropenia, thrombocytopenia) and stomatitis/mucositis than sorafenib. In sub-analysis, Asian patients treated with sorafenib reported a longer PFS than those treated with sunitinib (HR=0.87, 95% CI: 0.83-0.90, P = 0.01), and European patients treated with sunitinib had a longer OS than those treated with sorafenib (HR=1.17, 95% CI: 1.01-1.30, P=0.04). Moreover, the pooled results of the high-quality studies reported a higher ORR with sunitinib than with sorafenib, and medium-quality studies showed a longer OS with sunitinib than with sorafenib. Conclusions: Sunitinib has more benefits (longer OS and better ORR) than sorafenib as a first-line therapy for mRCC. However, sunitinib has higher toxicity than sorafenib. Sorafenib might be more suitable than sunitinib among Asian patients, and sunitinib might be superior to sorafenib in European patients. Nevertheless, more large-scale, high-quality studies are required.